2017
DOI: 10.18632/oncotarget.21378
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone receptor isoforms, agonists and antagonists differentially reprogram estrogen signaling

Abstract: Major roadblocks to developing effective progesterone receptor (PR)-targeted therapies in breast cancer include the lack of highly-specific PR modulators, a poor understanding of the pro- or anti-tumorigenic networks for PR isoforms and ligands, and an incomplete understanding of the cross talk between PR and estrogen receptor (ER) signaling. Through genomic analyses of xenografts treated with various clinically-relevant ER and PR-targeting drugs, we describe how the activation or inhibition of PR differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 68 publications
(166 reference statements)
6
51
0
Order By: Relevance
“…PR isoforms have different binding sites in chromatin, and the coregulators associated with PR isoforms are different (1); more recent studies have expanded the repertoire of isoformspecific PR binding partners as measured by Rapid Immunoprecipitation Mass Spectrometry of Endogenous proteins (RIME) (2). Distinct but overlapping gene sets are regulated by two major PR isoforms which can form either homodimers or heterodimers at hormone-responsive elements in chromatin.…”
Section: Pr Isoformsmentioning
confidence: 99%
See 2 more Smart Citations
“…PR isoforms have different binding sites in chromatin, and the coregulators associated with PR isoforms are different (1); more recent studies have expanded the repertoire of isoformspecific PR binding partners as measured by Rapid Immunoprecipitation Mass Spectrometry of Endogenous proteins (RIME) (2). Distinct but overlapping gene sets are regulated by two major PR isoforms which can form either homodimers or heterodimers at hormone-responsive elements in chromatin.…”
Section: Pr Isoformsmentioning
confidence: 99%
“…PR-B (but not PR-A) primarily cross-talks with ER at estrogen-regulated genes via direct association as measured by co-IP and ChIP assays performed in human breast cancer cell lines and breast tumors (3), as well as in intact cells by proximity ligand assays (TH Truong and CA Lange unpublished data). The ER/PR interaction with c-Src kinase and hormone-dependent activation of downstream MAPKs was first defined by seminal studies in 1998 (4) and a role for ER/PR transcriptional complexes in the regulation of global gene expression was later demonstrated by gene profiling and RIME studies performed in breast cancer models (2,3,5).…”
Section: Pr Isoformsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Singhal et al reported that in T47D xenografts, the antiprogestin telapristone (TLP) induced transient inhibition of tumor growth, while the combined administration together with tamoxifen induced an almost complete tumor regression (Singhal et al 2016). A similar effect was obtained with two other antiprogestins: CDB 4453 and EC313 (Singhal et al 2018). These results are in line with the inhibitory effect previously observed in T47D xenografts treated with MFP (Wargon et al 2015).…”
Section: Cell Line-derived Xenograft Modelsmentioning
confidence: 85%
“…Tumors were (Knutson et al 2012) and with our preclinical studies suggesting that PRB-H tumors may be endocrineresistant tumors (Lanari et al 2012, Wargon et al 2015. Singhal et al (2018) using the raw RNA-seq data from our study (Rojas et al 2017) compared the list of differential genes expressed in T47D-YA and T47D-YB xenografts and those differentially regulated in PRA-H or PRB-H patients and concluded that a high PRA/PRB ratio might correlate with worse prognosis. Although the total number of samples included in both studies coincides, for the PAM50 analysis, we excluded the HER2+ cases, a lobular tumor and a metastatic tumor from a premenopausal patient, to compare a homogeneous cohort of patients.…”
Section: Pr Isoforms In Breast Cancer Cohortsmentioning
confidence: 99%